1996
DOI: 10.1007/bf00188163
|View full text |Cite
|
Sign up to set email alerts
|

Functional organization of olfactory processing in the accessory lobe of the spiny lobster

Abstract: An isolated brain preparation was used to characterize neurons innervating the accessory lobe (AL) of the spiny lobster (Panulirus argus). Four distinct classes of neurons responded to electrical stimulation of the olfactory (antennular) nerve. These cells responded to electrical stimulation with a long and variable latency; they also responded to odor stimulation in a nose-brain preparation. Neurons connecting the AL with the olfactory lobe branched in the central AL layer and selectively innervated olfactory… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
78
1

Year Published

1997
1997
2010
2010

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(85 citation statements)
references
References 21 publications
6
78
1
Order By: Relevance
“…In contrast to the results obtained in crayfish, Schmidt (2001) concluded that nearly all adult-born cells in cluster 10 of P. argus remain within a portion of the cluster comprised mainly of OL projection neuron somata (Wachowiak and Ache 1994;Schmidt and Ache 1996;Wachowiak et al 1996), suggesting that most newborn cells in this species differentiate into OL projection neurons. While the functional importance of life-long neurogenesis in the olfactory pathways of decapod crustaceans remains unknown, these results suggest that its roles may differ amongst decapod taxa.…”
Section: Differentiation Of Newborn Cells In the Lpz (Cluster 10): Prcontrasting
confidence: 63%
See 3 more Smart Citations
“…In contrast to the results obtained in crayfish, Schmidt (2001) concluded that nearly all adult-born cells in cluster 10 of P. argus remain within a portion of the cluster comprised mainly of OL projection neuron somata (Wachowiak and Ache 1994;Schmidt and Ache 1996;Wachowiak et al 1996), suggesting that most newborn cells in this species differentiate into OL projection neurons. While the functional importance of life-long neurogenesis in the olfactory pathways of decapod crustaceans remains unknown, these results suggest that its roles may differ amongst decapod taxa.…”
Section: Differentiation Of Newborn Cells In the Lpz (Cluster 10): Prcontrasting
confidence: 63%
“…7A, B). As described above, although most neurons in cluster 10 express crustacean-SIFamide, the cluster is comprised of at least two classes of neurons: OL projection neurons and AL projection neurons (Wachowiak et al 1996;Sullivan and Beltz 2005b). These two neuronal classes have distinct structural and functional identities, OL projection neurons innervating the primary olfactory neuropil (the OL) and AL projection neurons innervating a higher-order multimodal neuropil (the AL).…”
Section: Differentiation Of Newborn Cells In the Lpz (Cluster 10): Prmentioning
confidence: 99%
See 2 more Smart Citations
“…The paired ALs in crustaceans receive no primary sensory input but rather receive projections of local interneurons in clusters 9 and 11 that carry higher-order visual, mechanosensory and olfactory information Wachowiak et al, 1996; J. M. Sullivan and B. S. Beltz, unpublished results). The AL output is carried by the axons of the cluster 10 projection neurons, which continue to proliferate throughout the animal's life (Harzsch et al, 1999;Benton and Beltz, 2002) and which project to the hemiellipsoid bodies located in the lateral protocerebrum ).…”
Section: Serotonergic Rhythms In the Olfactory And Accessory Lobesmentioning
confidence: 97%